2023
DOI: 10.1515/dmpt-2022-0157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of EPHX1 c.337 T>C and UGT2B7*2 genetic polymorphisms on the requirement of carbamazepine maintenance dose in persons with epilepsy (PWE) of Southern part of India: a cross-sectional genetic association study

Abstract: Objectives Carbamazepine (CBZ) is a first-line antiseizure drug used for focal onset seizures. It exhibits inter-individual variability in plasma carbamazepine levels and there are both genetic and non-genetic factors having a role in the requirement of CBZ maintenance dose. The aim was to study the influence of EPHX1 c.337 T>C and UGT2B7*2 genetic polymorphisms on CBZ maintenance dose requirement in persons with epilepsy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…23 It is well documented that genetic factors play a significant role in the modulation of anti-seizures medications efficacy, adverse effects, and dose changes such as phenytoin, carbamazepine, sodium valproate. 24,25 Enhanced gap junctional communication (GJC) between neurons is considered a major factor underlying the neuronal synchrony driving seizure activity. In drug-resistant epilepsy, connexins, as integral components of gap junctions, are implicated in several key processes contributing to the resistance to antiepileptic drugs (AEDs).…”
Section: Role Of Connexins In Epilepsymentioning
confidence: 99%
“…23 It is well documented that genetic factors play a significant role in the modulation of anti-seizures medications efficacy, adverse effects, and dose changes such as phenytoin, carbamazepine, sodium valproate. 24,25 Enhanced gap junctional communication (GJC) between neurons is considered a major factor underlying the neuronal synchrony driving seizure activity. In drug-resistant epilepsy, connexins, as integral components of gap junctions, are implicated in several key processes contributing to the resistance to antiepileptic drugs (AEDs).…”
Section: Role Of Connexins In Epilepsymentioning
confidence: 99%
“…(b) Histidine to arginine conversion on exon 4 increases the enzyme activity (Venkatraman et al, 2023).…”
Section: Pharmacogenomics: Cbz and Bdmentioning
confidence: 99%
“…[ 7 8 ] In South India, the minor allele frequencies of EPHX1 c. 337 T > C and UGT2B7*2 were 40%. [ 9 ] We reported that these genetic polymorphisms did not affect CBZ maintenance dose in South India,[ 10 ] and the impact of these genetic variants on the plasma CBZ levels and metabolic ratio is to be studied in PWE from South India for optimization of the drug therapy.…”
Section: Introductionmentioning
confidence: 99%